Pericardial Effusion With Tamponade in Lung Cancer Patients During Treatment With Nivolumab: A Report of Two Cases - Yamasaki, Masahiro; Daido, Wakako; Saito, Naomi; Funaishi, Kunihiko; Okada, Takenori; Kawamoto, Kazuma; Matsumoto, Yu; Matsumoto, Naoko; Taniwaki, Masaya; Ohashi, Nobuyuki; Hattori, Noboru (Frontiers in Oncology, 2019)
Background: Nivolumab is an immune checkpoint inhibitor that has shown efficacy for treating non-small cell lung cancer and has become a standard therapy for previously treated non-small cell lung cancer. Moreover, immune-related adverse events of immune checkpoint inhibitor therapy are well-known. Malignant pericardial effusions occasionally arise in patients with lung cancer. There have been a few reports of pericardial effusion in non-small cell lung cancer after nivolumab administration. However, the cause of this condition is controversial; the possibilities include serositis as an immune-related adverse event or pseudo-progression. Case presentation: This report presents two cases of pericardial effusion with tamponade in lung cancer during treatment with nivolumab. Both patients experienced temporal increases in pericardial effusions followed by effusion regression. In one case, nivolumab administration was continued after performance of pericardiocentesis, without an increase in pericardial effusion. In the other case, temporal simultaneous increases in both the pericardial effusion and the primary tumor were detected, followed by simultaneous regression in both the effusion and the tumor. These findings support the fact that the pericardial effusions were caused by pseudo-progression. Conclusions: Pericardial effusion with tamponade can occur in lung cancer patients being treated with nivolumab; moreover, some of these effusions might be caused by pseudo-progression. In the case of putative pseudo-progression, continuation of nivolumab administration might be allowable with strict follow up.